PENGEMBANGAN USAHA JAJANAN BALI DENGAN PENERAPAN ALAT DEEP FRYER DAN ALAT SEALER DI DESA CANDI KUNING - Pudja, I.A.R.P.; Widia, I W.; Arda, I G. (Buletin Udayana Mengabdi, 2016)
The aims of the activities of community service was to increase the economic value of Balinese snack and to implement of appropriate technology in the business development of traditional Balinese snack. The method of community service was field surveys and interviews, introducing the right technology equipment for business development of traditional Balinese snack, counseling and training of science and appropriate technology. In the implementation of community service, business partner of Balinese snack have been introduced and given deep fryer of traditional Balinese snack, given sealer for plastic packaging, training for the labeling on the packaging of traditional Balinese snack, monitoring and mentoring of production. The conclusion of this community service was the implementation of activities going on smoothly and there was a two-way discussion of the active participants with questions and responses to the topic. Activities like this was very useful for the people in the village. So that, the same activities need to be carried out in other villages that have the same agricultural commodities.
Keywords: deep fryer; sealer; Balinese snack; business; traditional